POLA KOMUNIKASI PIMPINAN DAN PENELITI DALAM INSTITUSI PENELITIAN DAN PENGEMBANGAN (LITBANG) PEMERINTAH - M. Bashori Imron (Pusbindiklat - LIPI, 2010)
Communication pattern is the circulation of information in a network of interdependent relationships with one another. Communication pattern is different in its implementation for the Management of Research and Development units derived from background research rather than researchers. Circulation of information from communications to the above, tend to be undertaken by a leader who belongs to the researchers. In contrast information from the communication down, tend to be undertaken by the leadership that does not come from a background of researchers. Emergence the different communication patterns among others, is also influenced by the encouragement of informal communications that are not structured and not fixed by the habits of the leadership itself. Communication processes are carried out continuously and continuous between leaders and researchers in reducing the differences will lead to convergence of communication that can form a patterned process of communication.